DEVELOPMENT OF BI-MODAL EXERCISE BICYCLE FOR PHYSICAL FITNESS AND REHABILITATION (Nigerian Journal of Technology, 2018)
Exercise bicycles are used for kinesiological activities; to increase general fitness, and for training for cycling events. They are also used for weight loss. The aim of this study is to produce a special exercise bike which allows for both upper and lower limbs pedalling either independently or otherwise. The manufacturing processes employed in the design involved the use of AutoCAD design suite and other production engineering processes which included material selection and acquisition, cutting, welding and drilling. The device was tested for both comfort and effectiveness for cardiac rehabilitation using the rate of heartbeat as the test parameter. A strong positive correlation was found (p